2015
DOI: 10.5812/ijp.368
|View full text |Cite
|
Sign up to set email alerts
|

Aortic Intima-Media Thickness and Mean Platelet Volume in Children With Type 1 Diabetes Mellitus

Abstract: Background:Diabetes mellitus type 1 is the most common endocrine metabolic disorder occurring in childhood and adolescence due to the autoimmune destruction of pancreatic beta cells as a result of various environmental factors interacting with an underlying genetic predisposition. Diabetes is a risk factor for early onset atherosclerosis, and the high mortality rate seen in these patients is partially related to cardiovascular diseases.Objectives:This study was conducted to compare mean platelet volume as a ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 20 publications
1
29
0
Order By: Relevance
“…In this study, the STZ injection significantly increased the thickness of tunica media and aortic wall. In human studies, tunica media thickness of aorta increased significantly in diabetes compared with that of healthy people [45,46]. The present study showed that quercetin administration ameliorated the thickness of aortic wall and organization of elastic fibrils.…”
Section: Discussionsupporting
confidence: 61%
“…In this study, the STZ injection significantly increased the thickness of tunica media and aortic wall. In human studies, tunica media thickness of aorta increased significantly in diabetes compared with that of healthy people [45,46]. The present study showed that quercetin administration ameliorated the thickness of aortic wall and organization of elastic fibrils.…”
Section: Discussionsupporting
confidence: 61%
“…Ulutaş et al (42) also reported a positive correlation between MPV level and HbA1c level, which is following our results. Hekimsoy et al (43), have shown the opposite, while Ersoy et al (44), reported similar MPV values in children diagnosed with T1DM to those in a control group (8.74 ± 0.96 and 8.49 ± 0.66, respectively). These different results in platelet count could be explained by their dependency on several variables, such as mean platelet survival, platelet production rate, and turnover rate in diabetes mellitus.…”
Section: Spearman Correlation Analysismentioning
confidence: 89%
“…Type 1 diabetes mellitus (T1DM) is one of the most common endocrinological disorders in children and adolescents (1,2). It is caused by various environmental factors interacting with an underlying genetic predisposition resulting in autoimmune destruction of pancreatic beta cells (3,4). The onset of type 1 diabetes mellitus occurs early in life and children affected are at great risk of developing microvascular and macrovascular complications and cardiovascular disease later as a complication of diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…Various different studies have thus suggested that platelets can be used as a marker for predicting an increase in the risk of the micro-and macrovascular complications of diabetes [13][14][15]. However, Ersoy et al [16] reported similar MPV values in children diagnosed with T1DM to those in a control group (8.74 ± 0.96 and 8.49 ± 0.66, respectively), although correlation was determined between intima-media thickness and MPV values. Similarly, in our study, we determined no statistically significant difference in MPV values between children with T1DM and the control group.…”
Section: Discussionmentioning
confidence: 99%